Drei Phasen Die Debatte zur Qualitätsentwicklung in der Lehrer_innenbildung - Pasternack, Peer (GEW-Materialien aus Hochschule und Forschung, 2017)
The study analyses the quality development of teaching staff at schools. It looks at all three phases of training: Study, probation and further training. The expert's report therefore gives a comprehensive overview of the structure of further training for teachers in the Federal Republic of Germany's federal education system.